Laparoscopic sleeve gastrectomy without an over-sewing of the staple line - Kasalicky, Mojmir; Michalsky, David; Housova, Jitka; Haluzik, Martin; Housa, Daniel; Haluzikova, Denisa; Fried, Martin (Obesity surgery, 2008)
BACKGROUND: In the past few years, laparoscopic sleeve gastrectomy (LSG) became a widely used bariatric method. Based on results of recent LSG studies, LSG is being increasingly used even as a single bariatric method. On contrary with some other reports, we do not reinforce the LSG staple line with over-sewing. Our pilot study presents treatment outcomes and results 18 months after LSG. METHODS: Sixty-one consecutive morbidly obese (MO) patients (19 male and 42 female) who underwent LSG from January 2006 to May 2008 were included into the study. The mean age, height, and weight were 37.3 years (29-57), 168 cm (151-187), and 118 kg (97-181), respectively, while mean body mass index (BMI) was 41.8 (36.1-60.4). LSG started at 6 cm from pylorus and ended at the angle of Hiss. For gastric sleeve calibration 38F, intragastric tube was used. All 61 LSG were performed without over-sewing of the staple line. In the last 24 cases, the staple line was covered with Surgiceltrade mark strips, which were however placed without any fixation to the underlying gastric tissue. RESULTS: Mean operating time was 105 min (80-170) and no conversion to open surgery. An 18-month follow-up was recorded in 39 MO patients. The mean weight loss was 31.3 (range, 21-67 kg) and mean % excess BMI loss reached 72% (range, 64-97%). Neither leak nor disruptions of the staple line and/or sleeve dilatation were recorded. CONCLUSION: LSG is an effective and safe bariatric procedure with low incidence of complications and mortality in our experience.
Keywords: index tělesné hmotnosti; Treatment Outcome; Weight Loss; Gastrectomy; Retrospective Studies; Cohort Studies; výsledek terapie; Middle Aged; mužské pohlaví; Laparoscopy; gastrektomie; Adult; kohortové studie; Body Mass Index; ženské pohlaví; retrospektivní studie; Humans; hmotnostní úbytek; lidé středního věku; Surgical Stapling; chirurgická technika pomocí přístrojů a svorek; dospělí; Female; laparoskopie; Obesity, Morbid; lidé; Male; morbidní obezita